Trends in achieving nutritional status aged 0-23 months based on the TB/U index against the median line for 2019-2022 in Madina Regency - Tampubolon, Yessi Septia; Sinaga , Haripin Togap; Sitinjak , Evlin SH (Jurnal Ilmiah Kesehatan, 2024)
Child growth trends are used to compare weight gain and body length or height with standard weight gain and body length or height gain. Based on data from the 2021 Indonesian Nutrition Status Survey (SSGI) in North Sumatra Province in Madina Regency. The prevalence of stunted children (TB/U) is 47.7%. Based on 2018 Riskesdas survey data in North Sumatra Province in Madina Regency. The prevalence of stunted children (TB/U) is 17.3%. Determine the trend in achieving nutritional status aged 0-23 months based on the TB/U index against the 2019-2022 Median Line in Madina Regency (Secondary Data Analysis). The method used in this research is secondary data. Secondary data is data obtained through relevant agencies in the form of documents or references related to the problem being studied. The data source in this research is e-PPGBM data in Madina Regency from 2019 to 2022. Results in the graph of male and female toddlers, the z-score of female toddlers is closer to the median line. A line graph goes up and down (zigzag) on the male line graph, which could cause invalid data.